2017
DOI: 10.1532/hsf.1898
|View full text |Cite
|
Sign up to set email alerts
|

Open Cardiac Surgery without Blood and Blood Products Transplantation

Abstract: We have performed a total of 138 cases; no blood and blood products were transfused in 71% (n = 98), and in 29.0% (n = 40) blood and blood products were transfused. Thirty-day mortality and morbidity (arrhythmia, infectious and pulmonary morbidity, myocardial infarction, cerebrovascular accident, renal dysfunction, sternal revision) were compared between these two groups and no statistically significant difference was observed. Patients' awakening, extubation time, cardiopulmonary bypass period, cross-clamp ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The amount of hemorrhage and transfusion required in hypothermic patients during CPB was reported higher than in normothermic patients in recent studies [Ho 2011;Rasmussen 2007]. Since we consider blood transfusion to be a type of tissue transplantation, we perform open heart surgery without using blood and blood products in our clinical practice to avoid transfusion-related side effects as much as possible, as reported in a previous study [Kaplan 2017].…”
Section: Discussionmentioning
confidence: 90%
“…The amount of hemorrhage and transfusion required in hypothermic patients during CPB was reported higher than in normothermic patients in recent studies [Ho 2011;Rasmussen 2007]. Since we consider blood transfusion to be a type of tissue transplantation, we perform open heart surgery without using blood and blood products in our clinical practice to avoid transfusion-related side effects as much as possible, as reported in a previous study [Kaplan 2017].…”
Section: Discussionmentioning
confidence: 90%
“…hemoglobin values but also on the hemodynamic and clinical parameters of our patients [Kaplan 2017]. By this method, we did not use any blood or blood products also for this patient.…”
Section: E10mentioning
confidence: 96%
“…An analysis of transfusion practice in Australian hospitals revealed that transfusion rates varied across hospitals from >1 RBC unit from 22% to 67% and >5 RBC units from 5% to 25%, with the hospital characteristics having no bearing on this practice. 31 No doubt, appropriate use of allogeneic blood can be lifesaving, but many transfusions are not only unnecessary but can be harmful. 32 This becomes even more relevant in a scenario in which the patient is more likely to experience bleeding, such as during cardiac surgery.…”
mentioning
confidence: 99%